2011
DOI: 10.1111/j.2042-3306.2011.00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of subchondral cystic lesions of the medial femoral condyle of mature horses with growth factor enhanced chondrocyte grafts: A retrospective study of 49 cases

Abstract: SummaryReasons for performing study: To evaluate the long-term clinical outcome after allogeneic chondrocyte and insulin-like growth factor-I (IGF-I) grafting of subchondral cystic lesions (SCLs) of the femoral condyle in horses. Objective: To test the hypothesis that chondrocyte and IGF-I grafts will improve the long-term clinical outcome in arthroscopically debrided SCLs. Methods: Medical records of 49 horses with SCLs of the femoral condyle treated by debridement and implantation of chondrocytes and IGF-I w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
78
0
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(91 citation statements)
references
References 32 publications
3
78
0
10
Order By: Relevance
“…Therefore, they are not suited for reconstruction of the weightbearing joint surface (Hurtig et al, 2001). In a recent equine study, a 74% success rate was reported when treating subchondral bone cysts of the MFC with cancellous bone grafts covered by growth-factor-enhanced chondrocytes (Ortved et al, 2012). However, histological examination of the resulting surface was not performed in that clinical case series.…”
mentioning
confidence: 89%
“…Therefore, they are not suited for reconstruction of the weightbearing joint surface (Hurtig et al, 2001). In a recent equine study, a 74% success rate was reported when treating subchondral bone cysts of the MFC with cancellous bone grafts covered by growth-factor-enhanced chondrocytes (Ortved et al, 2012). However, histological examination of the resulting surface was not performed in that clinical case series.…”
mentioning
confidence: 89%
“…Conservative treatment consists of a rest period out at grass, followed by gradual return to full training (Jeffcott and Kold 1982), or controlled exercise and systemic administration of NSAIDs, often in combination with intra-articular medication (Trotter and Dyson 2003). However, since the outcome of conservative treatment of SCLs is generally poor, surgical intervention is currently the recommended treatment option (McIlwraith 2013), especially in older horses, or in horses that are refractory to conservative treatment (Ortved et al 2012, Smith et al 2005. Since SCLs of the PIP joint are not arthroscopically accessible, surgical debridement is usually performed through a transcortical approach (Fürst et al 1997, Mettenleiter 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact mechanism of the anabolic effect with PTH is not clear, its main function is attributed to stimulating osteoblast proliferation (Rubin and Bilezikian 2003). Treatment of equine SCLs using insulin-like growth factor (IGF)-1 in combination with allogeneic chondrocytes led to improved healing in the short-term (8 weeks) and long-term (8 months) follow-up with a successful outcome in 80 % of horses over 3-years-ofage, even in the presence of joint degeneration (Ortved et al 2012). It has been suggested that horses older than three years tend to be more refractory to the previously described treatments; Smith et al (2005) found that only 35 % of horses older than 3 years became sound after surgical debridement of an SCL in the medial femoral condyle.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Cell-based therapy for the repair of articular cartilage injury [4][5][6] has been pursued due to the poor intrinsic healing of injured cartilage, 2 the poor long-term response to surgical therapies, 7 and the lack of effective disease-modifying osteoarthritis drugs. 8,9 Repair with chondrocyte grafts improves long-term outcome, 10 but must be either allogeneic, with risk of immune rejection, 11,12 or autologous, with donor-site morbidity and added complexity. 13 Adult bone marrowderived mesenchymal stem cells (MSCs) are a stem cell source for autologous cell transplantation to musculoskeletal tissues with minimal donor-site morbidity, and good proliferative and chondrogenic potential.…”
Section: Introductionmentioning
confidence: 99%